Prawo karne Królestwa Polskiego w latach 1815−1905 a sprawowanie kultu religijnego - Paweł Ludwiczak (Czasopismo Prawno-Historyczne)
The article pertains to the law in force in the Kingdom of Poland between 1815 and 1905. Furthermore, it indicates the changes which were brought about by the liberalization of statutes and regulations concerning faith in 1906. The main aim is to familiarize readers with the contemporary criminal law pertaining strictly to conducting private and public services as well as to draw attention to regulations delineating missionary work. The paper is general in character because presenting a detailed picture of each faith with an enumeration of their legal, civil and political limitations is a topic for a more comprehensive study.